Deviation and Social Control. The History and Theory of Sociology of Deviation - Zdanevičius, Arnas (Sociologija. Mintis ir veiksmas, 2000)
The aim of the article is to discuss the concepts of deviation and social control which are relatively new in the Lithuanian discourse of sociology. The author takes his point of departure in an attempt to understand the limits of the concepts and starts his discussion from the suggestion of Colin Sumner that the attempts to define what is deviant behaviour led the sociology of deviation to a dead end. The author suggests that the defining question that grounds the concepts is a question anomie. He argues for a definition of the concepts built around the tension between an effort to attain an orderly state of being on the one hand and the threat of disciplinary control on the other.
Keywords: deviation; social control; history of sociology; Colin Sumner